Sistem Analisis Desain Pembangkit Listrik Tenaga Surya Kapasitas 50 WP - Nasution, Elvy Sahnur; Suriadi; Azhar (Yayasan Kawanad, 2022)
The need for electricity is good for the industry, offices, and public and individuals are greatly increased. However, the increase in demand for electricity is not accompanied by the additional power supply. Based on these problems, chosen solar energy as an alternative energy to generate electric power. A tool that is used here is the solar cell because it can directly convert solar radiation into electrical energy (photovoltaic process). So that solar energy can be used at night, then during the day, the electrical energy generated is stored before a battery which is controlled by the regulator. Regulator output is directly connected to the inverter from the DC to AC. The test results of solar modules (photovoltaic) indicated that the results of the average power output reached 38.24 Watt, and the currents were 2.49 A. This is because the photovoltaic follows the direction of movement of the sun and always located at the photovoltaic to remain facing the sun. Therefore, it will still be able to capture the radiant sun to the fullest.